2012
DOI: 10.1177/011719681202100105
|View full text |Cite
|
Sign up to set email alerts
|

Foreigners Cometh! Paths to Multiculturalism in Japan, Korea and Taiwan

Abstract: This paper has a four-fold goal: (1) it examines the difficulties faced by Japan, Korea and Taiwan in developing and implementing multicultural programs for their newly arriving migrants; (2) it offers an analysis of indigenous ethnic formation and migration of workers and marriage migrants in the context of ongoing debates on multiculturalism in East Asia; (3) it analyzes narratives behind the educational reforms to shed light on the political contention surrounding multicultural governance in the region; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 43 publications
(50 reference statements)
0
7
1
Order By: Relevance
“…As a result of an investigation into the type of relationship that Latin American professionals have with Korea's sociocultural characteristics in their immigration experiences, it was found that they employ adaptation strategies, such as the formation of limited social networks and the reconstruction of their racial identity. Unlike previous studies on immigration that have focused on immigrants from Asia and unskilled workers (Kim & Oh, 2012), this study showed that Latin American professionals experience Korean society in a relatively different way and that how they express themselves also involves distinct characteristics. For those involved mainly in organizational life, such as in sports, the Latin American professionals who are not familiar with the Korean hierarchy perceive a cultural difference.…”
Section: Discussioncontrasting
confidence: 81%
“…As a result of an investigation into the type of relationship that Latin American professionals have with Korea's sociocultural characteristics in their immigration experiences, it was found that they employ adaptation strategies, such as the formation of limited social networks and the reconstruction of their racial identity. Unlike previous studies on immigration that have focused on immigrants from Asia and unskilled workers (Kim & Oh, 2012), this study showed that Latin American professionals experience Korean society in a relatively different way and that how they express themselves also involves distinct characteristics. For those involved mainly in organizational life, such as in sports, the Latin American professionals who are not familiar with the Korean hierarchy perceive a cultural difference.…”
Section: Discussioncontrasting
confidence: 81%
“…In industrialized Asian countries, especially Japan, Taiwan, and South Korea, migration has been increased since 1990s. Labor and marriage migration take the biggest proportion of migration to Japan, Taiwan, and South Korea because working age population has decreased due to low-birth rate [ 1 ]. The increase of marriage migrants could ingenerate the social issues including ethnic tensions, and it also happens in South Korea (hereafter Korea).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the political view in South Korea seems to be in favor of foreign teachers, especially since the English language learning has become a business that many companies are benefiting from. The government supports bringing in foreign teachers to teach English, and the people also support having foreign teachers in schools and academies to learn English (Kim & Oh, 2012). Both sides seem to hold the view that it is to better communicate with tourists and to better compete in the international business scene.…”
Section: South Koreamentioning
confidence: 99%